The right of the unborn against eugenics through the selection of embryosin in vitro fertilization - Galiano Maritan, Grisel; Morffi Collado , Claudia Lorena; León Fadraga, Geanny (Revista Universidad de Guayaquil, 2020)
The analysis of the new eugenics and its use in in vitro fertilization raises serious legal dilemmas between the desire to conceive, the protection of the embryo and the genetic identity and individuality of the unborn. In vitro fertilization, a technique that is part of a medical procedure for fertilization using an extracorporeal medium, has been transformed through the preselection of embryos. The main objective of the research is to analyze the repercussions of the application of eugenics as an embryo pre-selection criterion in in vitro fertilization, for the fulfillment of this purpose, methods and techniques of a social investigation of a legal nature are used within which are They find: the historical-logical analysis; the exegetical - analytical method; the comparative method; the case study and, of course, the bibliographic analysis